2021
DOI: 10.1111/1477-9552.12454
|View full text |Cite
|
Sign up to set email alerts
|

Energy and crop price cycles before and after the global financial crisis: A new approach

Abstract: Using the newly developed Hamilton filter, we decompose prices of three primary energy sources (crude oil, coal and natural gas) and five significant crops (corn, palm oil, rice, soybean and wheat) to isolate their cyclical components. Then, we apply time-difference analyses to study their co-movement. Analysing 15 energy price-crop price pairs over two periods, 1990-2009 and 2010-2020, we find that the correlations between coal and crop prices have weakened significantly during the 2010s, while correlations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…The choice of p is especially important in making comparisons across seasonally adjusted and unadjusted time series. In a recent study, Vatsa and Miljkovic (2022) also applied the HF to study the linkages between monthly global energy and crop prices. They assigned a value of 12 to p. Hamilton (2018) demonstrated that the HF is robust to various techniques that are used to seasonally adjust the data.…”
Section: The Methodological Frameworkmentioning
confidence: 99%
“…The choice of p is especially important in making comparisons across seasonally adjusted and unadjusted time series. In a recent study, Vatsa and Miljkovic (2022) also applied the HF to study the linkages between monthly global energy and crop prices. They assigned a value of 12 to p. Hamilton (2018) demonstrated that the HF is robust to various techniques that are used to seasonally adjust the data.…”
Section: The Methodological Frameworkmentioning
confidence: 99%
“…When the US dollar is strong, grain sellers get paid less for their commodity, and when it's weak, they get paid more. Wheat prices are negatively affected by a strong US currency and a weak US dollar [12]. The United States dollar is the primary reserve currency used throughout the world.…”
Section: Value Of Us Dollarmentioning
confidence: 99%
“…The Commodity Research Bureau (CRB) Index plots the price of a basket of commodities against the U.S. dollar index. This index measures how well the dollar performs compared to other currencies [12].…”
Section: Value Of Us Dollarmentioning
confidence: 99%
“…As opposed to them, Fulzele et al (2022), Pilloni et al (2022), Vatsa and Miljkovic (2022) in their writings point out the increasingly growing need for energy resources and, in particular, fossil fuel energy, to accelerate the recovery of the global economy from the COVID-19 crisis. Gargallo et al (2022), Ram and Webler (2022), Tan et al (2021), Zhang et al (2022) in their publications maintain that the world community is not ready to completely abandon fossil fuel energy and that clean energy involves certain constraints that are associated with its incomplete coverage of economic entities (constraints of infrastructure), high cost (financial constraints), as well as low and unpredictable performance (natural and climatic constraints of renewable energy sources).…”
Section: Theoretical Mechanism and Hypothesis Built-upmentioning
confidence: 99%